One-step synthesis of polyhedral silsesquioxanes bearing bulky substituents: UV-MALDI-TOF and ESI-TOF mass spectrometry characterization of reaction products - Fasce, Diana Patricia (2001)
The NaOH-catalyzed hydrolytic condensation of the reaction product between N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and phenyl glycidyl ether (PGE) was followed by matrix-assisted ultraviolet laser desorption/ionization time-of-flight mass spectrometry (UV-MALDI-TOF MS) and electrospray ionization time-of-flight mass spectrometry (ESI-TOF MS). After 24 h at 50 °C, main condensation products were a mixture of perfect and imperfect polyhedra:  T8, T9(OH), and T10, with traces of T7(OH) and T11(OH). Every one of these products was composed of a series of peaks in the mass spectra, accounting for the incomplete reaction of PGE with the aminosilane (e.g., T8 showed the presence of the species containing 24 PGE units arising from the complete reaction of the initial silane, as well as species containing 23, 22, and 21 PGE units). A thermal treatment to 150 °C led to the appearance of extra peaks corresponding to intramolecular dehydration products. Peaks corresponding to the loss of one water molecule from T9(OH) and T7(OH) were present and could be ascribed to the reaction between SiOH and a secondary OH group. Dehydration products from T8 and T10 were observed, as well as species arising from the loss of two water molecules from T9(OH) and T7(OH). A plausible explanation for the presence of these peaks is the rupture of a Si−O−Si bond in the presence of NaOH, followed by condensation of the resulting fragments with secondary OH groups.